2012
DOI: 10.1167/iovs.12-10495
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Susceptibility to Apoptosis in Human Retinal Pigment Epithelial Cells Is Triggered by Disruption of p53–Mdm2 Association

Abstract: PURPOSE.Relatively little is known about the contribution of p53/Mdm2 pathway in apoptosis of retinal pigment epithelial (RPE) cells or its possible link to dysfunction of aging RPE or to related blinding disorders such as age-related macular degeneration (AMD).METHODS. Age-associated changes in p53 activation were evaluated in primary RPE cultures from human donor eyes of various ages. Apoptosis was evaluated by activation of caspases and DNA fragmentation. Gene-specific small interfering RNA was used to knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 71 publications
4
53
0
1
Order By: Relevance
“…HNE is known to induce apoptosis, which is also a characteristic of aging RPE cells, a phenomenon which has been implicated in the early pathogenesis of AMD (Bhattacharya et al, 2012;Kook et al, 2008;Sharma et al, 2008). We demonstrated here that quercetin could protect stressed ARPE-19 cells from HNE-induced cytotoxicity and decrease the release of three inflammatory mediators, IL-6, IL-8, and MCP-1 when compared to cells treated with HNE and the equivalent amount of quercetin diluent DMSO.…”
Section: Discussionmentioning
confidence: 64%
“…HNE is known to induce apoptosis, which is also a characteristic of aging RPE cells, a phenomenon which has been implicated in the early pathogenesis of AMD (Bhattacharya et al, 2012;Kook et al, 2008;Sharma et al, 2008). We demonstrated here that quercetin could protect stressed ARPE-19 cells from HNE-induced cytotoxicity and decrease the release of three inflammatory mediators, IL-6, IL-8, and MCP-1 when compared to cells treated with HNE and the equivalent amount of quercetin diluent DMSO.…”
Section: Discussionmentioning
confidence: 64%
“…We have previously shown that aging in human RPE cells activates p53-mediated apoptosis through increased level and post-translational modification of p53, increased levels of the pro-apoptotic marker PUMA, activation of caspase-3, increased levels of CDKN1A, a known transcriptional target of p53, and reduced levels of antiapoptotic BCL2, all of which lead to an overall increase in apoptosis (Bhattacharya et al 2012, 2011). To investigate age-related changes in p53-mediated senescence and inflammation pathways, we measured the levels of p53 and its target proteins in primary RPE cultures from young and aged donors.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, p53 regulates innate immune mediated processes, including increased expression of TLRs, cytokines and chemokines, enhancement and stimulation of IFN signaling, IFN regulatory factor-9, and regulates expression of IFN stimulated genes and IFI family genes, (Gugliesi et al 2005; Kwak et al 2003; Menendez et al 2013, 2011; Munoz-Fontela et al 2008; Shatz et al 2012). Aging in the RPE is associated with increased p53 levels and increased p53-mediated apoptosis (Bhattacharya et al 2012). Thus p53 may play an important role in regulating aging in the RPE and in development of AMD.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we showed that blockage of H3R17 asymmetric dimethylation attenuated hyperglycemia-induced RPE cell apoptosis. Indeed, p53 and its target genes induce RPE cells apoptosis [32][33][34]. Hence, one can imagine, perhaps when RPE cells exposes to hyperglycemia, CARM1 and dimethylated H3R17 being recruited to p53 responsive elements of apoptotic target gene promoter regions to induce RPE cells apoptosis.…”
Section: Discussionmentioning
confidence: 99%